2016
DOI: 10.1007/s10068-016-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterococcus faecalis EF-2001 on experimentally induced atopic eczema in mice

Abstract: Here, the effects of heat-killed Enterococcus faecalis EF-2001 (EF-2001) on atopic eczema (AE) were assessed. An AE model was established in vivo by repetitious topical exposure to 1-chloro-2,4-dinitrobenzene (CDNB) and dermatophagoidesfarinae extract (DFE) via application on each ear. Mice were administered EF-2001 orally for 4 weeks, dermal and epidermal ear thickness, mast cell infiltration of the ear tissue, and serum IgE and IgG2a levels were evaluated. Moreover, pathogenic cytokines levels of the ears, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Such compounds are immunogenic and can activate macrophages, thereby contributing to the inflammatory process [ 51 ]. Human IgE antibody regulation could be affected in allergy or atopy, by Enterococcus [ 52 , 53 ]. We found elevated proportions of Enterococcus in infected persons, and increased IgE levels were associated with urogenital schistosomiasis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds are immunogenic and can activate macrophages, thereby contributing to the inflammatory process [ 51 ]. Human IgE antibody regulation could be affected in allergy or atopy, by Enterococcus [ 52 , 53 ]. We found elevated proportions of Enterococcus in infected persons, and increased IgE levels were associated with urogenital schistosomiasis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EF-2001 treatment groups were administrated orally and daily gavage doses of EF-2001 for 16 days, then colitis was induced in the three experimental groups by rectal administration of 4% DNBS in 50% ethyl alcohol for two days (Fig 1A). The dosages of EF-2001 were determined by previous reports [17,18]. All animal care procedures and experiments were approved by the Institutional Animal Care and Use Committee of Konkuk University (KU15113).…”
Section: Methodsmentioning
confidence: 99%
“…The DAI is the combined score of weight loss compared to initial weight, stool consistency, and bleeding. Scores are defined as follows: weight loss: 0 (no loss), 1 (1–5%), 2 (5–10%), 3 (10–20%), and 4 (>20%); stool consistency: 0 (normal), 2 (loose stool), and 4 (diarrhea); and bleeding: 0 (no blood), 1 (Hemoccult positive), 2 (Hemoccult positive and visual pellet bleeding), and 4 (gross bleeding, blood around anus) [18].…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers reported that a mixture of various heatkilled L. acidophilus strains strongly released TNF-α and NO [39] and that heat-killed Enterococcus faecalis alleviated atopic symptoms in mice by reducing the IgE level, expression level of CDNB/DFE-induced inflammatory cytokines, and infiltration of mast cells [40]. Kim et al [41] showed that the viable and heat-killed LAB isolated from mukeunji showed different patterns of TNF-α and IL-6 production between species.…”
Section: Immune-stimulating Activity Of Heat-killed Lactobacillus Spementioning
confidence: 99%